Ultrasonographic diagnosis of early pregnancy in cattle using different ultrasound systems - Racewicz, Przemysław; Sickinger, Marlene; Włodarek, Jan; Jaśkowski, Jędrzej M. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2016)
Objective: To evaluate the efficiency of different ultrasound devices in achieving an early diagnosis of pregnancy in dairy herds. Material and methods: A total of 1976 Holstein Friesian cows and heifers were artificially inseminated (AI) according to the herd manager’s regime. Pregnancy diagnostics were performed between day 26 and 35 after AI using six different types of ultrasound systems (linear vs. sector scanners). Manual rectal palpation between day 45 and 60 after AI was used as the gold standard for pregnancy diagnostics. Sensitivity (SENS), specificity (SPEC), positive (PPV) and negative predictive value (NPV) and diagnostic accuracy (ACC) of the diagnostic measures were determined. Results: Average SENS was 82% (range 67.7–95.2%) with a mean SPEC of 73% (range 50.0–81.0%). ACC was 78.2% with a minimum of 64.6% and a maximum of 89.4%, depending on the ultrasound system. The PPV (ratio of the number of pregnant cows with a positive examination result to the number of cows actually pregnant) was 80.8% (range 59.1–88.1%), whereas the NPV (defined as the ratio of the number of cows correctly diagnosed negative to the number of cows actually open) was 74.4% (72.3–91.9%). Significant differences for these parameters were found depending on the ultrasound system used (p ≤ 0.01; Cramer’s V. = 0.14). Conclusion and clinical relevance: Regardless of the ultrasound device used, early pregnancy diagnostics between day 26 and 35 show a moderate diagnostic efficiency. Comparing the accuracy of the different devices, there may be a significant influence of type and technical parameters. Even though ultrasound systems with mechanical sector probes are not as convenient to use as systems with linear probes, according to this study, sector scanners are a reasonable alternative.
Keywords: Ultrasound; linear and sector scanner; bovine fertility; sensitivity; specificity